The Effective Teaching Method of Pharmacology for the Students in the Faculty of Health and Nutrition in Tabriz University of Medical Sciences - Moslem Najafi; Tahereh Eteraf-Oskouei (Tabriz University of Medical Sciences, 2013)
Introduction: Pharmacology is one of the specific courses of the medical sciences students. Multiplicity of drugs and a lot of similarities in their characteristics make the learning of this lesson difficult and no common methods of teaching have been able to fix this problem so far. This study aimed to examine the effect of observing the dosage forms appropriate to each training session on enhancing learning pharmacology and comparing it with other traditional teaching methods. Methods: Fifty six Health Care Management and Family Health students in Tabriz University of Medical Sciences participated in this descriptive study. Each session was held using lectures and PowerPoint during half of educational classes and the other half was conducte d using whiteboard and at the same time the teaching pharmaceutical dosage forms, their functions and properties were shown. A standardized questionnaire based on Likert scale was given to the students and the level of learning was reviewed by self-assessment method. The data were analyzed using SPSS and descriptive statistical parameters. Results: Teaching pharmacology through showing pharmaceutical dosage forms had significant effect on improving students learning in both fields based on their self-assessment, so that more than 95% of students were satisfied with the teaching methods. From point view of students, the understanding of pharmacology using whiteboard and showing pharmaceutical dosage forms was significantly more than PowerPoint. Conclusion: The students believe that the level of the learning pharmacology through using whiteboard along with observing the dosage forms appropriate to each training session is outstanding.